Enhanced Third Degree Burn Wound Healing by Hypoxic Mesenchymal Stem Cells’ Secretome: IL-10 Upregulation and TNF-α/PGE2 Suppression - Dirja, Bayu Tirta; Wardoyo, Eustachius Hagni; Putra, Agung; Amalina, Nur Dina (Trends in Sciences, 2024)
Background: Severe third-degree burns pose a notable obstacle in clinical settings, frequently leading to hindered healing of wounds and the development of scars. In this research, we explored how the secretome of hypoxic mesenchymal stem cells (HS-MSCs) could be improved the healing of burn wounds. Methods: In this study, we used 20 male Wistar rats that induced third degree wound by metal 80 exposure for 10 s. These rats divided into 4 groups: Healthy, control, HS-MSCs 100 µL, and HS-MSCs 200 µL groups. We injected the HS-MSCs, which carry various beneficial molecules like IL-10, TGF-β, PDGF, and VEGF, directly into the skin in a third-degree burn rat model on day 1 after burn induction, and harvest on day 14. Results: Our research discovered that using HS-MSCs resulted in a dosage-related rise in IL-10, an anti-inflammatory cytokine, alongside a notable decrease in TNF-α and PGE2, pro-inflammatory cytokines. These effects quickened the healing process by improving re-epithelialization and minimizing scar formation. Conclusions: Our findings indicate that HS-MSCs show promise as a treatment for severe burns by potentially controlling inflammation and fostering a regenerative healing process. More investigation is needed to understand the exact mechanisms and to explore how HS-MSCs could be applied in clinical treatments. HIGHLIGHTS HS-MSCs suppress inflammation and promote regenerative healing in severe burns HS-MSCs accelerated re-epithelialization and reduced scarring GRAPHICAL ABSTRACT